The Time Course of Name Retrieval During Multiple-Object Naming: Evidence From Extrafoveal-on-Foveal Effects. - Malpass, Debra; Meyer, Antje S. (Journal of Experimental Psychology. Learning, Memory & Cognition, 2010)
The goal of the study was to examine whether speakers naming pairs of objects would retrieve the names of the objects in parallel or in sequence. To this end, we recorded the speakers' eye movements and determined whether the difficulty of retrieving the name of the 2nd object affected the duration of the gazes to the 1st object. Two experiments, which differed in the spatial arrangement of the objects, showed that the speakers looked longer at the 1st object when the name of the 2nd object was easy than when it was more difficult to retrieve. Thus, the easy 2nd-object names interfered more with the processing of the 1st object than the more difficult 2nd-object names. In the 3rd experiment, the processing of the 1st object was rendered more difficult by presenting it upside down. No effect of 2nd-object difficulty on the gaze duration for the 1st object was found. These results suggest that speakers can retrieve the names of a foveated and an extrafoveal object in parallel, provided that the processing of the foveated object is not too demanding.